Centella asiatica (L.) Urban: From Traditional Medicine to Modern Medicine with Neuroprotective Potential - Orhan, Ilkay Erdogan (Hindawi Ltd, 2012)
This paper covers the studies relevant to neuroprotective activity of Centella asiatica (L.) Urban, also known as Gotu Kola. The plant is native to the Southeast Asia and has been used traditionally as brain tonic in ayurvedic medicine. The neuroprotective effect of C. asiatica has been searched using the key words Centella, Centella asiatica, gotu kola, Asiatic pennywort, neuroprotection, and memory through the electronic databases including Sciencedirect, Web of Science, Scopus, Pubmed, and Google Scholar. According to the literature survey, C. asiatica (gotu kola) has been reported to have a comprehensive neuroprotection by different modes of action such as enzyme inhibition, prevention of amyloid plaque formation in Alzheimer's disease, dopamine neurotoxicity in Parkinson's disease, and decreasing oxidative stress. Therefore, C. asiatica could be suggested to be a desired phytopharmaceutical with neuroprotective effect emerged from traditional medicine.
Keywords: Neuronal Dendritic Arborization; Oxidative Stress; Antioxidant Activity; Alzheimers-Disease; Contact-Dermatitis; Extract; Acid; Plants; Triterpene; Cognition